Role of three-dimensional computed tomography with humeral subtraction in assessing anteromedial facet coronoid fractures - Moayd Abdullah H Awad, MBBS, FRCSC; Michael Lapner, MD, FRCSC; Armin Badre, MD, MSc, FRCSC (JSES International, 2025)
Background: The anteromedial facet (AMF) of the coronoid is a key structure in resisting varus posteromedial rotatory instability (PMRI) of the elbow. However, not all isolated coronoid fractures involve the AMF and not all fractures involving the AMF are the result of a PMRI mechanism. There is debate regarding the management of isolated coronoid fractures. A reliable method of differentiating this heterogeneous group of isolated coronoid fractures is essential to develop an appropriate management algorithm. The aim of this study was to evaluate the role of additional humeral subtraction three-dimensional (3D) images in the detailed assessment of the known radiographic features of AMF fractures with PMRI mechanism. Methods: Three upper extremity fellowship-trained orthopedic surgeons evaluated 32 consecutive CT scans in patients with isolated coronoid fractures, on two occasions separated by at least 5 months. On each occasion, CT scan images were evaluated for fracture morphology and orientation in two rounds. In the first round, the evaluation was made based on all two-dimensional and 3D reconstruction images of the entire elbow; in the second round, the surgeons had access to images from the first round plus 3D reconstruction with humeral subtraction. Statistical analysis to assess agreement amongst the surgeons was performed using the kappa multirater analysis. Intraobserver agreement was evaluated using Pearson’s correlation coefficient. Results: The addition of the humeral subtraction view significantly improved the interobserver agreement for fracture morphology from 0.28 (95% confidence interval [CI] 0.07-0.49) to 0.66 (95% CI 0.46-0.87), P < .001; and for orientation from 0.31 (95% CI 0.09-0.52) to 0.54 (95% CI 0.31-0.77), P < .001. Similarly, the intraobserver Pearson correlation improved from 0.28-0.38 to 0.48-0.76 for fracture morphology, and from 0.36-0.77 to 0.51-0.69 for fracture orientation. Conclusion: 3D CT reconstruction with humeral subtraction improved surgeons’ ability to characterize radiographic features of AMF coronoid fractures. Future studies are required to determine whether better characterization of the morphology and orientation of AMF fractures allows for the categorization of these fractures into more homogenous groups and the development of more consistent management algorithms.